Rethinking Artificial Intelligence in Early Childhood Education for Best Global Practice in Primary Schools in Odeda Local Government, Ogun State - Dagunduro, Olayinka Morenike; Taiwo F. Ogunyemi; Damilola Christianah Adebowale (International Journal on Integrated Education, 2025)
The paper examines the rethinking artificial intelligence in early childhood education for best global practice in primary schools in Ogun state. The study adopted a descriptive survey research design. Population comprises about 250 primary schools’ teachers in Odeda Local Government, Ogun state, Nigeria. The sample size for this study comprises of ten (10) primary schools in Odeda Local Government area of Ogun State in which ten (10) teachers were selected to make a total of 100 respondents for the study. A self-developed questionnaire was used as instrument for data collection. It was developed in closed-ended of Agree or disagree. The instrument was moderated by experts who affirmed its validity. Reliability of the instrument was determined using Cronbach Alpha and the value of 0.62 was obtained which is reliable enough for this study. Data collected were analyzed using simple percentage, mean and standard deviation statistical tools. Findings align with global studies that emphasize both the benefits and challenges of AI integration in education that AI can significantly enhance personalized learning, access to the necessary infrastructure and teacher training remains critical for successful implementation. Similarly, findings in Ogun State reflect these global trends, where AI implementation is gaining momentum but still requires targeted improvements in teacher training and infrastructure to maximize its potential. Findings also emphasize the effectiveness of AI-driven assessment systems in reducing teachers' workloads and providing immediate feedback.  It was therefore recommended that Ogun State Ministry of Education should invest in teacher training programmes to build capacity for effectively integrating AI tools into classrooms, ensuring educators can maximize the benefits of AI in teaching and learning. Also, schools in Ogun State should implement AI-driven personalized learning platforms to tailor educational experiences to individual student needs, thereby improving engagement and academic performance.